E-commerce in trade agreements: India's strategies and options - Pritam Banerjee; Arpita Mukherjee; Aahana Srishti (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2024)
The e-commerce sector is rapidly growing globally with the Asia-Pacific region accounting for 58 per cent of global retail e-commerce in 2022, and India, Singapore, China, and Japan leading this growth. The discussion on e-commerce and trade at the global level began in 1998 with the establishment of the Working Programme on E-commerce (WPEC) at the World Trade Organization (WTO), under which members agreed to a moratorium on customs duties for electronic transmissions. Progress on broader e-commerce trade rules within WPEC has been slow, which prompted the creation of the Joint Statement Initiative (JSI) on E-commerce in 2019. On July 26, 2024, 80 member countries reached a consensus on trade rules in a "stabilized text." Simultaneously, many nations have pursued standalone digital trade agreements or included digital trade chapters in broader trade agreements. India has not joined the JSI and opposes a permanent moratorium, citing evolving definitions of e-commerce and potential tariff revenue losses for developing countries. However, India has signed an agreement with a digital trade chapter with the United Arab Emirates and is negotiating similar chapters with other important trade partners. Given this background, the paper presents the discussions on e-commerce in the WPEC and the JSI. It presents India's position in the WTO and trade agreements, its concerns, domestic regime and negotiating strategies and options. It provides data driven analysis of the impact of the moratorium on India's e-commerce trade and suggests why digital taxation may be better than a tariff for revenue collection. It compares India's autonomous regime (AR) with JSI obligations. It analyses trade agreements across parameters related to cross-border e-commerce trade, with a focus on agreements in the APAC region, in terms of their scope, coverage and depth of commitments. The paper concludes by providing a roadmap to move forward with discussions in the JSI and recommendations for India to find its stand in global negotiations.
hdl:20.500.12870/7750
Keywords: F13; F68; O19; 330; E-commerce; India; Trade Agreements; Cross-border trade; WTO